2015
DOI: 10.1007/s00442-015-3254-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting growth responses of dominant peatland plants to warming and vegetation composition

Abstract: There is growing recognition that changes in vegetation composition can strongly influence peatland carbon cycling, with potential feedbacks to future climate. Nevertheless, despite accelerated climate and vegetation change in this ecosystem, the growth responses of peatland plant species to combined warming and vegetation change are unknown. Here, we used a field warming and vegetation removal experiment to test the hypothesis that dominant species from the three plant functional types present (dwarf-shrubs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…The microenvironmental drivers examined in the present study (i.e., water level and shading) mediate the effect of macroclimate on Sphagnum processes on a local scale. There are experiments that indicate that warming may indirectly promote Sphagnum growth by increasing the growth of dwarf shrubs in the bog‐fen complex, which promote Sphagnum growth via a shading effect cooling the peat surface (Walker, Ward, Ostle, & Bardgett, ). Indeed, we found that growth and mass loss would be higher in shaded conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The microenvironmental drivers examined in the present study (i.e., water level and shading) mediate the effect of macroclimate on Sphagnum processes on a local scale. There are experiments that indicate that warming may indirectly promote Sphagnum growth by increasing the growth of dwarf shrubs in the bog‐fen complex, which promote Sphagnum growth via a shading effect cooling the peat surface (Walker, Ward, Ostle, & Bardgett, ). Indeed, we found that growth and mass loss would be higher in shaded conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bias was similar in each plot, thus making species frequencies comparable among treatments, and did not further influence the response of plant species to treatments. We especially distinguished the graminoid cover from the ericoid cover as these two plant types differ in productivity, litter, root inputs and plant–fungal associations, and as such may have different effects on ecosystem C dynamic (Robroek et al., , ; Walker, Ward, Ostle, & Bardgett, ; Walker et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Northern peatlands are dominated by four vegetation types, namely bryophytes, graminoids, dwarf‐shrubs and trees (not naturally present in UK peatlands) (Rodwell, ), which differ considerably in their ecophysiological traits. For example, Sphagnum moss species produce decay‐resistant litter that promotes low rates of soil respiration (Dorrepaal et al ., ), but are expected to have limited influence at the ecosystem level due to their low productivity relative to dwarf‐shrubs and graminoids (Walker et al ., ). By comparison, the ubiquitous graminoid Eriophorum vaginatum grows rapidly and generates litter that is decomposable (Trinder et al ., ), leading to greater rates of decomposition and short‐term carbon turnover (Ward et al ., , ).…”
Section: Introductionmentioning
confidence: 99%